Feasibility Study of Coconut Oil Factory Business in Banyuasin Regency, South Sumatra Using a Feasibility Study Approach - Priantama, Dimas Bayu; Bayuaji, Ridho (Inovbiz: Jurnal Inovasi Bisnis, 2024)
Coconut oil is a global commodity with increasing demand. Indonesia, as the world's largest producer of coconut oil, is still unable to meet market demand. Therefore, the construction of a domestic coconut oil processing factory is very necessary. This research aims to analyze the business feasibility of building a coconut oil factory in Banyuasin Regency, South Sumatra. The research methods used include analysis of internal and external aspects, IFAS-EFAS analysis, SWOT analysis, PESTEL analysis, and business model canvas. The results of the analysis show that in general this business is feasible considering the market prospects and availability of supporting raw materials. the most influential internal factor is the availability of raw materials (coconut) due to the high demand for coconut oil, while production capacity still does not meet this need. Meanwhile, the most influential external factor is the demand for coconut oil, so demand becomes an opportunity in building a coconut oil factory. The construction of a coconut oil factory in Banyuasin Regency can achieve success if it pays attention to influential internal and external aspects, as well as implementing strategies to exploit potential or prevent problems from the development. A deep understanding of internal and external aspects will help factory makes the right decisions and ensure successful operations in Banyuasin Regency, South Sumatra.